2004
DOI: 10.1111/j.0269-2813.2004.01807.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of functional gastrointestinal disorders on health‐related quality of life: a population‐based case–control study

Abstract: SUMMARYBackground: The health-related quality of life is impaired in patients with functional gastrointestinal disorders seen in referral centres. Aim: To determine whether the health-related quality of life is impaired in subjects with functional disorders in the community and whether any differences can be explained by psychological co-morbidity. Methods: In a population-based, nested, case-control study, subjects reporting symptoms of either dyspepsia or irritable bowel syndrome and healthy controls were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
139
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(152 citation statements)
references
References 52 publications
(89 reference statements)
9
139
0
4
Order By: Relevance
“…In IBS factors predicting health-related QOL are a combination of psychiatric disorders (depressive, panic, or neurasthenia) or symptoms (easily fatigued and low in energy) and severe bowel symptoms, notably pain 24 . Health-related QOL is impaired in IBS and dyspepsia sufferers compared with healthy controls 25,27 . A recent thorough study found how the degree of somatization mediates the negative effect of anxiety and depression on the physical component score of the Medical Outcomes Scale SF-36 (limitations on daily life imposed by the illness, associated bodily pain, and impaired physical functioning) 25 .…”
Section: Inflammatory Bowel Diseases and Quality Of Lifementioning
confidence: 91%
See 1 more Smart Citation
“…In IBS factors predicting health-related QOL are a combination of psychiatric disorders (depressive, panic, or neurasthenia) or symptoms (easily fatigued and low in energy) and severe bowel symptoms, notably pain 24 . Health-related QOL is impaired in IBS and dyspepsia sufferers compared with healthy controls 25,27 . A recent thorough study found how the degree of somatization mediates the negative effect of anxiety and depression on the physical component score of the Medical Outcomes Scale SF-36 (limitations on daily life imposed by the illness, associated bodily pain, and impaired physical functioning) 25 .…”
Section: Inflammatory Bowel Diseases and Quality Of Lifementioning
confidence: 91%
“…The number of patients with chronic functional gastrointestinal disorders is increasing and consequently the prevalence of psychiatric disorders. It is widely recognized that people with IBD have impaired health-related QOL 20,23 , but recent studies emphasized concurrent anxiety and depressive and panic disorders as major causes of this impairment 24,25 . In dyspepsia, psychological distress is a better predictor of health-related QOL than the severity of the dyspepsia 26 .…”
Section: Inflammatory Bowel Diseases and Quality Of Lifementioning
confidence: 99%
“…The prevalence of dyspepsia in the community varies between 5% and 40%, depending on the geographical region under study, but also on the criteria used to define its presence. [1][2][3][4] The condition has significant implications both for sufferers, due to impaired quality of life and sickness absence from work, [5][6][7][8][9] and society as a whole, due to medical expenses arising from managing the condition. A recent questionnaire survey reported that the mean yearly cost of dyspepsia to patients was almost $700, 10 and burden of illness studies in the USA estimated that there were almost 2 million physician visits in 2009 as a result of dyspepsia, 11 and >30% of endoscopies were performed with dyspepsia as the main indication.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons have only been made in studies reporting significant impact of HRQoL among patients with dyspepsia that included FD as a subgroup. 14,15 In their review, El-Serag and Talley 16 concluded that to optimally measure the outcomes in FD trials in terms of HRQoL, future studies should match an appropriate sample of control subjects without FD by age and sex with patients with FD. With this directive in mind, as well as the fact that there are few reports on FD from a gender perspective, we constructed a population-based casecontrol study and survey investigating HRQoL in men and woman with FD.…”
Section: Introductionmentioning
confidence: 99%